CHARACTERIZATION OF MICROSATELLITE MARKERS FOR BACCHARIS DRACUNCULIFOLIA (ASTERACEAE) - Belini, Camila M. B. [UNESP]; Marques, Marcia O. M.; Figueira, Glyn M.; Bajay, Miklos M.; Campos, Jaqueline B.; Viana, Joao P. G.; Pinheiro, Jose B.; Zucchi, Maria I. (Botanical Soc Amer Inc, 2016)
Premise of the study: Baccharis dracunculifolia (Asteraceae) is a native plant of the Atlantic Forest that is used for the production of essential oil. Microsatellite markers were developed for this species to investigate the genetic diversity of three natural populations. Methods and Results: Seventeen out of 27 microsatellite loci identified in a genomic library used for the characterization of 315 individuals derived from three natural populations of B. dracunculifolia resulted in successful amplifications. Eleven polymorphic loci, ranging from two to seven alleles per locus, were obtained with expected and observed heterozygosity values ranging between 0.068 and 0.775 and 0.046 and 0.667, respectively. Conclusions: The microsatellite loci described in this study are tools that can be used for further studies of population genetics of B. dracunculifolia with a focus on deforested areas and conservation of natural populations.
Keywords: altitude; Asteraceae; Baccharis dracunculifolia; microsatellites; population genetics